Effect of Progressive Lumbar Stabilization Exercises Among University Students with Non-Specific Low-Back Pain Over Post-COVID-19 - Fariba Hossein Abadi, Mohansundar Sankaravel, Fairus Fariza Zainudin, Gunathevan a/l Elumalai, Ali Md Nadzalan (Tanjung Malim, 2024)
Effect of Progressive Lumbar Stabilization Exercises Among University Students with Non-Specific Low-Back Pain Over Post-COVID-19 by Fariba Hossein Abadi, Mohansundar Sankaravel, Fairus Fariza Zainudin, Gunathevan a/l Elumalai, Ali Md Nadzalan